PENGARUH PERBANDINGAN TEPUNG HANJELI (Coix lacryma-Jobi, L.) DENGAN BUAH SALAK KERING (Salacca edulis Reinw.) TERHADAP KARAKTERISTIK SNACK BAR - Saraswati, Ni Putu Putri Dewanty; Ekawati, I Gusti Ayu; Putra, I Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPA, 2019)
This study aims to determine the effect of hanjeli flour and dried snake fruit to the characteristics of snack bar produced and the right ratio of hanjeli flour and dried snake fruit that is able to produce snack bar with the best characteristics. The Completely Randomized Design was used in the research with treatment that is the ratio of hanjeli flour and dried snake fruit which consist of 5 levels: 90 %: 1 0%; 8 0%: 2 0%; 7 0%: 3 0%; 6 0%: 4 0%; 5 0%: 5 0% . The treatment was repeated 3 times to obtain 15 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan test. The result showed that hanjeli flour and dried snake fruit had a significant effect on water content, ash content, fat content, protein content, carbohydrate content, coarse fiber content, hardness, color (hedonic), aroma (hedonic), texture (hedonic and scoring), taste (hedonic) and overall acceptance (hedonic). Comparison of 50% hanjeli flour : 50% dried snake fruit produces snack bar with the best characteristics, namely: water content 18.43%, ash content 1,82%, fat content 16.63%, protein content 7.84%, carbohydrate content 55.29%, crude fiber content 3,14%, calori total 402,10 kcal, color liked, aroma very liked, texture little crumbly and liked, taste liked and overall acceptance liked.